Solve 39 mod 11 using:
Modular exponentiation
n is our exponent = 9
y = 1 and u ≡ 3 mod 11 = 3
See here
Since 9 is odd, calculate (y)(u) mod p
(y)(u) mod p = (1)(3) mod 11
(y)(u) mod p = 3 mod 11
3 mod 11 = 3
Reset y to this value
u2 mod p = 32 mod 11
u2 mod p = 9 mod 11
9 mod 11 = 9
Reset u to this value
9 ÷ 2 = 4
Since 4 is even, we keep y = 3
u2 mod p = 92 mod 11
u2 mod p = 81 mod 11
81 mod 11 = 4
Reset u to this value
4 ÷ 2 = 2
Since 2 is even, we keep y = 3
u2 mod p = 42 mod 11
u2 mod p = 16 mod 11
16 mod 11 = 5
Reset u to this value
2 ÷ 2 = 1
Since 1 is odd, calculate (y)(u) mod p
(y)(u) mod p = (3)(5) mod 11
(y)(u) mod p = 15 mod 11
15 mod 11 = 4
Reset y to this value
u2 mod p = 52 mod 11
u2 mod p = 25 mod 11
25 mod 11 = 3
Reset u to this value
1 ÷ 2 = 0
We have our answer